Experimental study on impact of high voltage power transmission lines on silicon photovoltaics using artificial neural network - Javed, Muhammad Rameez; Hussain, Muhammad Imtiaz; Usman, Mudassar; Asghar, Furqan; Shahid, Muhammad; Amjad, Waseem; Lee, Gwi Hyun; Waleed, Aashir (Frontiers in Energy Research, 2023)
The recent trend of renewable energy has positioned solar cells as an excellent choice for energy production in today's world. However, the performance of silicon photovoltaic (PV) panels can be influenced by various environmental factors such as humidity, light, rusting, temperature fluctuations and rain etc. This study aims to investigate the potential impact of high voltage power transmission lines (HVTL) on the performance of solar cells at different distances from two high voltage levels (220 KV and 500 KV). In fact, HVTLs generate electromagnetic (EM) waves which may affect the power production and photocurrent density of solar cells. To analyze this impact, a real-time experimental setup of PV panel is developed (using both monocrystalline and polycrystalline solar cells), located in the vicinity of 220 KV and 500KV HVTLs. In order to conduct this study systematically, the impact of HVTL on solar panel is being measured by varying the distance between the HVTL and the solar panels. However, it is important to understand that the obtained experimental values alone are insufficient for comprehensive verification under various conditions. To address this limitation, an Artificial Neural Network (ANN) is employed to generate HVTL impact curves for PV panels (particularly of voltage and current values) which are impractical to obtain experimentally. The inclusion of ANN approach enhances the understanding of the HVTL impact on solar cell performance across a wide range of conditions. Overall, this work presents the impact study of HVTL on two different types of solar cells at different distances from HVTL for two HV levels (i.e., 220 KV and 500 KV) and the comparison study of HVTL impact on both monocrystalline and polycrystalline solar cells.